A Study on Digital Service Innovation Factors Influencing Organization Performance: Ajman Police Department In UAE - Qaid Al-Subaihi, Ghazi Yaseen; Salim, Siti Aisyah (International Journal of Sustainable Construction Engineering and Technology, 2023)
The study presented an analysis of the influence of four digital services innovation groups of factors on organizational performance. It identified 20 digital services innovation factors, which were categorized into four groups namely participation, inter-organizational collaboration, reflexivity, and responsiveness. The study focused on the Ajman Police Department in the United Arab Emirates and collected data through a structured questionnaire survey using a purposeful random sampling technique among the employees of the department that involved 368 completed responses from the employees. Statistical analysis was conducted using SPSS software. The study found that the five highest ranked factors by the respondents, which significantly impact organizational performance, are PP1 (Customer Feedback and Surveys), OC1 (Partnership with Complementary Service Providers), RF1 (Ethical Evaluation of Service Offerings and Practices), PP2 (Employee Brainstorming Sessions), and RS3 (Ongoing Market Research and Competitor Analysis). Additionally, the study established a mathematical model to predict organizational performance based on the four variables: participation, inter-organizational collaboration, reflexivity, and responsiveness. Furthermore, the study revealed that all five groups of factors, including organizational performance factors, are significantly correlated. This research contributes to the understanding of the impact of digital services innovation on organizational performance, shedding light on the specific factors that play a crucial role in driving organizational success in the digital era. The findings provide valuable insights for organizations seeking to leverage digital services innovation to enhance their performance and competitiveness